Review of Hybrid Diesel–Solar Power System from Technical and Economic Perspectives at Power Plants in Lombok - Jawoto Tri Prabowo; Lilly S. Wasitova; Abdul Multi (Green Publisher, 2026)
Diesel Power Plants remain the main electricity source in Indonesia’s archipelagic country and they are served as isolated power systems, that characterized by high fuel consumption, high operating costs, and significant greenhouse gas emissions. This study evaluates the technical, economic, reliability, environmental, and diesel reduction performance of a hybrid Diesel Power Plants system integrated with solar power and battery energy storage. A quantitative simulation-based approach using HOMER software compares three configurations: conventional Diesel Power Plants, Diesel–Solar PV, and Diesel–Solar PV–BESS. The analysis focuses on energy performance, fuel efficiency, economic indicators, system reliability, and carbon dioxide (CO₂) emissions. Results show that integrating a 1 MWp PV system and a 1 MWh BESS into a 6 MW Diesel Power Plant in Lombok significantly improves system performance, reducing Specific Fuel Consumption by 4.70% and CO₂ emissions by 4.41%. Economically, the hybrid system lowers Net Present Cost by 3.31%, Operating Cost by 4.78%, and Levelized Cost of Energy by 3.58% to 0.2234 USD/kWh, with a payback period of 2.91 years, while also improving system reliability through reduced unmet load and capacity shortage. These findings confirm that the Diesel Power Plant–Solar PV–BESS configuration is a reliable, cost-effective, and environmentally sustainable diesel reduction solution for island-based power systems in Indonesia.